Photocurrent as a multiphysics diagnostic of quantum materials - Ma, Qiong (2023)
The photoexcitation life cycle from incident photon (and creation of photoexcited electron–hole pair) to ultimate extraction of electrical current is a complex multiphysics process spanning across a range of spatiotemporal scales of quantum materials. Photocurrent is sensitive to a myriad of physical processes across these spatiotemporal scales, and over the past decade it has emerged as a versatile probe of electronic states, Bloch band quantum geometry, quantum kinetic processes and device characteristics of quantum materials. This Technical Review outlines the key multiphysics principles of photocurrent diagnostics, for resolving band structure and characterizing topological materials, for disentangling distinct types of carrier scattering that can range from femtosecond to nanosecond timescales and for enabling new types of remote-sensing protocols and photocurrent nanoscopy. These distinctive capabilities underscore photocurrent diagnostics as a novel multiphysics probe for a growing class of quantum materials with properties governed by physics spanning multiple spatiotemporal scales.